2023
DOI: 10.1073/pnas.2205315120
|View full text |Cite
|
Sign up to set email alerts
|

Ecological marginalization is widespread and increases extinction risk in mammals

Abstract: Human land-use results in widespread range change across taxa. Anthropogenic pressures can result in species’ realized niches expanding, shifting, or contracting. Marginalization occurs when contraction constrains species to the geographic or ecological extremes of their historic niche. Using 4,785 terrestrial mammal species, we show that range contraction results in niche space and habitat diversity loss. Additionally, ecological marginalization is a common consequence of range contraction caused by human lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Recent studies have demonstrated that species performance trends and extinction risks are better explained by the distance to the species' ecological niche centroid rather than their geographic range centre (Britnell et al, 2023;Martínez-Meyer et al, 2013). Conditions at the range centre are rarely the same as those seen at niche centres (Britnell et al, 2023). The predictions of Caughley et al (1988) also assumed limiting factors, such as climate and resource use, acted independently and varied consistently across species ranges (Gaston, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated that species performance trends and extinction risks are better explained by the distance to the species' ecological niche centroid rather than their geographic range centre (Britnell et al, 2023;Martínez-Meyer et al, 2013). Conditions at the range centre are rarely the same as those seen at niche centres (Britnell et al, 2023). The predictions of Caughley et al (1988) also assumed limiting factors, such as climate and resource use, acted independently and varied consistently across species ranges (Gaston, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, an underappreciated factor is that PAs may be located within marginal habitats for the species they intend to protect (Kerley et al, 2012(Kerley et al, , 2020. Human pressures have pushed many mammal species towards their historic niche margins where they experience greater extinction risk (Britnell et al, 2023). In mild cases, there is large variation in PA effectiveness as species are protected as 'partial refugees' in both optimal and sub-optimal habitats (Lea et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined above, species vary in the amount of decline or even whether or not performance declines at all away from the niche centre and towards presumably marginal climates (Pironon et al, 2017; Sporbert et al, 2020; but see Britnell et al, 2023; Fristoe et al, 2023). We propose that functional traits may help explain species' ability to increase performance under non‐optimal climate conditions.…”
Section: Introductionmentioning
confidence: 99%